Matching Municipal Challenges and Resources: Intergovernmental Options - Spruce, Christopher (Maine Policy Review, 1991)
For most of the era since 1960, when environmental policy and resource policy have been central public issues, the focus of public debates on those policies was at the federal and state levels. Now, more and more of the decisions and policies that will determine the quality of life for citizens are being made at the local level. There is concern over the ability of small governmental units, which often rely heavily on the New England tradition of volunteer government, to manage the new array of technical issues. Christopher Spruce asks if we should not think more carefully about the creation of an increasingly complex set of intergovernmental special districts at the municipal level. Might a single broad-based general governmental unit, perhaps a form of reinvigorated county-level government, provide a better umbrella for cooperative efforts by local governments?
Keywords: Maine local government; intergovernmental relations